MODULATORY ACTIVITY OF RESVERATROL AND ENVIRONMENTAL ENRICHMENT ON BEHAVIOURAL AND NEUROINFLAMMATORY RESPONSES OF MICE TREATED WITH ALUMINIUM CHLORIDE - SHEHU MUHAMMAD, MUSTAPHA; OLUSEGUN AYO, JOSEPH; MOHAMMED DANJUMA, NUHU; ABDULWAHAB, AL-HASSAN; ISA, AHMED-SHERIF; HUSSAINI UMAR, ABDULLAHI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The study investigated the modulatory activity of resveratrol and environmental enrichment (EE) on behavioural and neuroinflammatory responses of male mice treated with aluminium chloride (AlCl3). Sixty-three Swiss albino mice were divided into nine groups of seven animals each as follows; 0.2 mL normal saline/kg (control), 0.2 mL Carboxymethyl cellulose (CMC)/kg, Resveratrol (200 mg/kg), CMC 0.2 mL/kg + EE, AlCl3 (50 mg/kg), Resveratrol (200 mg/kg) + EE, AlCl3 (50 mg/kg) + Resveratrol (200 mg/kg), AlCl3 (50 mg/kg) + EE, and AlCl3 (50 mg/kg) + Resveratrol (200 mg/kg) + EE, respectively. All treatments were given oral and lasted for 8 weeks. Assessments of behaviour were carried out at 0, 4 and 8 weeks after treatments, followed by biochemical analyses. AlCl3 significantly (p < 0.05) induced motor endurance deficits at the fourth week which was improved by Resveratrol and EE. The concentration of NF-Kβ significantly decreased in AlCl3 when compared to AlCl3 + EE + resveratrol treated group. Furthermore, the concentration of TNF-α was significantly decreased in Resveratrol, and AlCl3 + EE treated groups, when compared to AlCl3 + EE + Resveratrol treatment group. AlCl3 induced motor function deficits, which was improved by Resveratrol and EE. Resveratrol treatment alone and EE + AlCl3 decreased biomarkers of neuro-inflammation.